Upaya Peningkatan Kemampuan Menulis Drama Siswa Kelas XI IPA 1 SMA Negeri 3 Woja Kabupaten Dompu - Adiprasetio Prabowo; Aidin; Wahyuddin (Yayasan Pembina Lembaga Pendidikan (YPLP) PGRI Kabupaten Sumbawa Barat - NTB - Indonesia, 2023)
Learning to write drama scripts for class XI IPA 1 SMA Negeri 3 Woja needs to be improved. The purpose of this study is to describe efforts to improve the ability to write drama scripts in class XI IPA 1 SMAN 3 Woja, Dompu Regency. Methods of data collection, namely the method of observation, documentation, interviews, and assignments. The results of this study found that efforts to improve the ability to write drama scripts in class XI IPA 1 SMA Negeri 3 Woja went through various stages, namely, lesson planning, learning implementation, learning observation, learning evaluation, and reflection. The results of this study concluded that the ability of students to write drama scripts in class XI IPA 1 SMA Negeri 3 Woja Dompu Regency for the 2023/2024 academic year consisted of individual and group abilities. Individual student abilities are as follows: a) the high ability group = 69%; b) the moderate ability group = 26.9%; c) the group with low ability = 4.1%. The group achievement index (GPA) of students is 72.07 and they are in the normal ability category. The process of learning to write drama scripts will increase, and students will be active as long as the teacher goes through the stages above and conducts learning according to the lesson plan and syllabus